Achieving Sustainable and Responsible Consumption Production Policy through Integrated Waste Management in Residential Areas - Resti Dian Luthviati (Contrarius, 2026)
Effective and sustainable waste management constitutes a central component of environmental governance and public health protection, particularly in residential areas located along the administrative borders of Surakarta City. Border settlements frequently experience disparities in infrastructure provision, limited supervisory control, and uneven public service delivery, which collectively weaken the effectiveness of integrated waste governance. This study analyzes the implementation of the regional regulatory framework on integrated waste management in these peripheral residential areas and evaluates the institutional, regulatory, and socio legal constraints that affect its practical operation. The research applies a qualitative design grounded in empirical fieldwork. The study collects primary data through structured interviews with relevant stakeholders and analyzes the data using a normative and comparative approach. It compares Indonesia’s waste governance practices with selected international models implemented in Germany, Japan, and Singapore to identify transferable principles and institutional mechanisms that may strengthen local implementation. The findings demonstrate that the regulatory framework provides a systematic structure for integrated waste management; however, implementation gaps persist. Limited public awareness, inadequate waste processing facilities, and weak inter institutional coordination significantly hinder policy effectiveness, particularly in border residential zones. The study concludes that the government must intensify community engagement strategies, strengthen environmental education programs, and enhance cross sectoral collaboration to ensure the realization of sustainable and responsible waste management in border areas.